Effect of WMA-RAP technology on pavement performance of asphalt mixture: A state-of-the-art review. (1st September 2020) - Guo, Meng; Liu, Haiqing; Jiao, Yubo; Mo, Liantong; Tan, Yiqiu; Wang, Dawei; Liang, Meichen
Abstract: Warm mix asphalt (WMA) can be mixed and compacted at low temperature to reduce energy consumption and greenhouse gas emissions. Reclaimed asphalt pavement (RAP) can save asphalt binder and aggregate, which can achieve the better reclaimed effects with the addition of rejuvenator. However, WMA and RAP have some shortcomings, respectively. Warm mix asphalt and Reclaimed asphalt pavement (WMA-RAP) technology may solve these problems when they are used together. This article reviews the literature on the applications of WMA-RAP and its effects on the performance of the asphalt mixture. Different types of WMA additives work differently on high temperature performance, low temperature and moisture susceptibility. WMA with a certain content of RAP showed satisfactory rutting performance and low temperature cracking resistance. The low temperature cracking resistance and moisture susceptibility of WMA-RAP mentioned in the literature is improved because of some kinds of rejuvenators. It is hoped that this review will help pavement engineers to better design the WMA-RAP. Highlights: Mechanisms, research approaches and road performances of WMA-RAP were summarized. The influence of WMA additive, RAP content and rejuvenator on road performances were discussed. WAM-RAP technology was reviewed and future researches were suggested.